2014
DOI: 10.1371/journal.pone.0107888
|View full text |Cite
|
Sign up to set email alerts
|

Aortic and Carotid Arterial Stiffness and Epigenetic Regulator Gene Expression Changes Precede Blood Pressure Rise in Stroke-Prone Dahl Salt-Sensitive Hypertensive Rats

Abstract: Multiple clinical studies show that arterial stiffness, measured as pulse wave velocity (PWV), precedes hypertension and is an independent predictor of hypertension end organ diseases including stroke, cardiovascular disease and chronic kidney disease. Risk factor studies for arterial stiffness implicate age, hypertension and sodium. However, causal mechanisms linking risk factor to arterial stiffness remain to be elucidated. Here, we studied the causal relationship of arterial stiffness and hypertension in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Similarly Dahl salt-sensitive hypertensive rats develop an increase in PWV that precedes the increase in blood pressure in response to salt loading 24 . Although these experimental animal models did not address the issue of aging, however, in reality, they do support the notion that the increase in PWV occurs independent of pressure changes.…”
Section: Beyond the 5th Decade Of Age: Central Arterial Mechanics Andmentioning
confidence: 99%
“…Similarly Dahl salt-sensitive hypertensive rats develop an increase in PWV that precedes the increase in blood pressure in response to salt loading 24 . Although these experimental animal models did not address the issue of aging, however, in reality, they do support the notion that the increase in PWV occurs independent of pressure changes.…”
Section: Beyond the 5th Decade Of Age: Central Arterial Mechanics Andmentioning
confidence: 99%
“…A recent example of the virtuous circle connecting experimental and real world recent findings in hypertension was offered by the concurrence of not only the results but also the timing of findings obtained from basic and epidemiological research studies funded by the NHLBI in an effort to clarify the relationship between arterial stiffening and hypertension. Several concurrent basic research studies confirmed that arterial stiffening preceded overt hypertension in different experimental models, including the elastin-deficient mice 16 , obese mice 17 , or stroke-prone Dahl salt-sensitive hypertensive rats 18 . The same temporal sequence, i.e.…”
Section: Building On Our Past Legacy and Present Strengthsmentioning
confidence: 90%
“…7 At this age, both stroke-prone and non-stroke-prone rats had similar blood pressure. However, at 16 weeks of age, stroke-prone Dahl-S rats started to show significantly higher blood pressure than non-stroke-prone Dahl-S rats, again consistent with the conclusion that arterial stiffness precedes hypertension.…”
Section: Introductionmentioning
confidence: 87%